SEMIOTIC ANALYSIS OF U MILD’S PRINTED ADVERTISEMENTS - LISNAWATI, UYUN (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: printed advertisement, sign, icon, symbol, index, U MildPrinted advertisement has a promotional function as medium to advertise a product. It implicity persuades people to create demand of product which is being advertised. In this study, the writer uses printed advertisement of U Mild as the object. The printed advertisement was analyzes by using Semiotic study. There are seven printed advertisements selected in different themes. There are two questions to be answered: (1) What kinds of sign are used in the printed advertisements of U Mild based on the typology of sign by Peirce ?; (2) What is the meaning of each sign in the U Mild printed advertisements?This study uses qualitative approach by document analysis that focuses on identifying sign. The writer collected the data by identifying the verbal and visual signs within seven U Mild’s printed advertisements. In analyzing the data, the writer applied  Peirce’s typhology of sign theory. The meaning of signs combination found in the seven advertisements is also analysed using connotation theory.The writer found 140 signs in total consisting of 70 icons, 37 indexes and 33 symbols. Each sign has a very important role to build up the message delivered by the advertisements. The sign has function to make particular message clear to support and to strengthen up the message.The researcher finally suggests that the next researchers analyze other objects as the data in conducting a research related to semiotics study like television, ballyhoo or newspaper in order to obtain various results. Different semiotics theory is also suggested to apply in order to broaden the semiotic analysis.